Pharmacological Prolyl Hydroxylase Domain Inhibition as a Therapeutic Target for Parkinson’s Disease - Rajagopalan, Subramanian; J. Chinta, Shankar; K. Andersen, Julie (CNS & Neurological Disorders - Drug Targets, 2014)
Previously published data from our laboratory demonstrated that pharmacological inhibition of a family of enzymes known as prolyl hydroxylase domain proteins prevents neurotoxicity associated with the acute 1-methyl-4- phenyl-1,2,3,6-tetrahydropyridine intoxication model of Parkinson’s disease in young animals. In this study, we assessed whether prolyl hydroxylase domain inhibition was neuroprotective in an inducible genetic dopaminergic glutathione depletion model previously characterized by our laboratory that more closely recapitulates the age-related and progressive nature of the human disease. Pharmacological prolyl hydroxylase domain inhibition via 3,4-dihydroxybenzoate was found to significantly attenuate hallmark mitochondrial dysfunction and loss of dopaminergic substantia nigral pars compacta neurons associated with this model. These studies further validate the possibility that prolyl hydroxylase domain inhibition may constitute a viable therapy for Parkinson’s disease.
Keywords: Parkinson’s disease